Religiosity and well-being: An IFLS study on differences between majority and minority religious groups - Anwar Iqbal (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: As a key component of well-being, happiness and life satisfaction are important issues of social welfare in sustainable development. In the context of Indonesia's multi-religious society, religiosity is believed to have an important role in shaping subjective well-being. However, the influence of religiosity on happiness may vary depending on the social position of religious groups. This study aims to examine the relationship between religiosity and subjective well-being by considering the role of religious groups (majority and minority) as moderating variables. Methods: The research data are sourced from the Indonesian Family Life Survey Wave 5 (IFLS-V) involving 24,596 adults aged 21-60 years (M = 37.4). The analysis was conducted using a moderation model with subjective well-being as the dependent variable, religiosity as the predictor variable, and religious group as the moderating variable. Findings: The results of the study indicate that religiosity has a positive role on each happiness (B = 0.068, 95% CI = 0.059 - 0.077) and life satisfaction (B = 0.156, 95% CI = 0.141 - 0.170). Minority religious groups tend to have lower levels of subjective well-being than majority religious groups. As a moderator variable, religious groups have a different role on the relationship between religiosity and each of the two indicators of subjective well-being. The religious group acts as a moderator between religiosity and happiness (B = 0.036, 95% CI = 0.006 - 0.065) where the effect is stronger for the non-Muslim group. However, the religious group does not moderate the relationship between religiosity and life satisfaction (B = 0.029, 95% CI = -0.019 - 0.077), so the effect of religiosity on increasing subjective well-being applies similarly for both groups. Conclusion: These findings confirm that the relationship between religiosity and subjective well-being is dichotomous and contextual, depending on the individual's socio-religious position. Novelty/Originality of this article: This article provides an original contribution by presenting national-scale empirical evidence on the differences in the role of religiosity on two indicators of subjective well-being between majority and minority groups in Indonesia.